AB1107-HPR Long Term Exercise Training Improves The Total Hip Arthroplastypatients' Ability To Forget Their Artificial Joint. (15th July 2016) - Onal, S.; Guney, H.; Kinikli, G.I.; Sarial, C.; Atilla, B.; Yuksel, I.
Abstract : Background: Total Hip Arthroplasty (THA) is among the most widely performed procedures in orthopedic practice and outcome studies consistently showed an overall satisfaction by both patients and physicians.The purpose of this study was to determine effect of exercise duration on the ability to forget the artificial joint, in hip osteoarthritis patients who underwent THA. Objectives: Forty-two patients (female=26, male=16) who underwent unilateral THA were included in the study. Patients were divided into two groups either to do exercise for less than 6 months (Group I; short term exercise, n=24) or over 6 months (Group II; long term exercise, n=18). Mean age was 53.9± 15.1 years, mean Body Mass Index (BMI) was 27.2 ± 5.2 kg/m 2 in Group I and mean age was 57.5 ± 13.3 years, mean BMI was 27.2 ± 5.2 kg/m 2 in Group II, respectively. Methods: Forgotten Joint Score (FJS) was applied to detect the patients' ability to forget the artificial hip joint after THA surgery. Western Ontario and McMaster Osteoarthritis Index (WOMAC) pain, stiffness and activity of daily living (ADL) questionnaire were used to determine the functional status. Intensity of pain was measured with visual analog scale (VAS). Statistical analysis of the data was performed with Mann Whitney-U test. Results: There were no differences in WOMAC stiffness scores (p=0.146) between groups. WOMAC pain scores (p=0.003), WOMAC ADL scores (p=0.019), VAS scores (p=0.000) were better in Group II. FJS scores (p=0.005) were in favor with Group II which the patients who were exercising more than 6 months. Conclusions: Exercise training over 6 months improves the THA patients' ability to forget their artificial joint. References: Learmonth ID, Young C, Rorabeck C. The operation of the century: Total hip replacement. Lancet 2007;370:1500–19 Gogla PP, Christensen CM, Schmidt C. Total hip replacement in patients with ostheoarthritis of the hip: improvements in pain and functional status.Orthopedics 1996; 19:873–5 Montin L, Leino-Kilpi H, Suominen T, Lepisto J. A systematic review of empirical studies between 1996 and 2005 of patient outcomes of total hip arthroplasty and related factors. J Clin Nurs 2008; 17: 40–5. Disclosure of Interest: None declared